1994
DOI: 10.1038/ki.1994.460
|View full text |Cite
|
Sign up to set email alerts
|

Selective trophic effect of L-carnitine in type I and IIa skeletal muscle fibers

Abstract: Biopsies were taken from the vastus lateralis muscle of 26 chronic uremic patients before and after a 24-week treatment with L-carnitine given at the dose of 2 g i.v. at the end of hemodialysis, or in dialysis solution, or per os twice daily. The aim of the study was to evaluate both the muscle morphology in dialyzed subjects and the modification provoked by the therapy. All patients manifested a significant, even if variable, degree of muscular atrophy which involved all types of muscle fibers. After the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 13 publications
3
39
2
Order By: Relevance
“…Some [39] but not all investigators report low plasma free carnitine in maintenance hemodialyzed patients [40, 41]. Moreover, a deficit in L -carnitine is responsible for atrophy of type I and IIA muscle fibers and is associated with an accumulation of intracytoplasmatic lipids which is not seen in muscular atrophy of the uremic patient [24, 42]. These findings in carnitine deficiency differ from these observed in CRF.…”
Section: Muscle Composition and Metabolism In Uremiacontrasting
confidence: 46%
See 2 more Smart Citations
“…Some [39] but not all investigators report low plasma free carnitine in maintenance hemodialyzed patients [40, 41]. Moreover, a deficit in L -carnitine is responsible for atrophy of type I and IIA muscle fibers and is associated with an accumulation of intracytoplasmatic lipids which is not seen in muscular atrophy of the uremic patient [24, 42]. These findings in carnitine deficiency differ from these observed in CRF.…”
Section: Muscle Composition and Metabolism In Uremiacontrasting
confidence: 46%
“…They also found the muscle fiber type composition to be similar to that observed in healthy men after an endurance training program. On the other hand, Giovenali et al [24] observed muscular atrophy involving all types of muscle fibers without accumulation of intracytoplasmatic lipid. Muscle protein metabolism is discussed in a later paragraph.…”
Section: Muscle Composition and Metabolism In Uremiamentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributable to the higher mitochondrial content and higher carnitine palmitoyl transferase 1 levels in type I compared with type II muscle fibers. In this context, it is worth noting that 24 wk of L-carnitine administration has been shown to have a selective trophic effect upon type I muscle fibers in man (17).…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine also improved nutritional parameters such as serum transferrin and albumin in HD patients [13,14]. Intravenous administration of L-carnitine (2 g) at the end of a HD session also increases the morphological diameters of skeletal muscle fibers [15]. L-carnitine treatment prevented deterioration of the peak rate of oxygen consumption (VO 2 max) [16].…”
Section: Effects On Nutritionmentioning
confidence: 99%